The Potency of Trichoderma sp. as A Biocontrol Agent against Fusarium sp. Pathogen of Porang (Amorphophallus muelleri Blume) Tuber - Nindi Nazula Fajarini; Rodiyati Azrianingsih; Suharjono Suharjono (Journal of Tropical Life Science, 2020)
Porang (Amorphophallus muelleri Blume) has high economic value in Asia. Porang tuber is high in glucomannan and thus becomes one of the exportable food commodities. Porang plants are susceptible to wilt disease caused by Fusarium sp. Trichoderma sp. has the ability to inhibit the growth of pathogenic fungi such as Fusarium sp. This research aimed to study the potency of Trichoderma sp. in controlling the growth of Fusarium sp. Trichoderma sp. was isolated from the rhizosphere soil in A. muelleri plantation, while Fusarium sp. was isolated from A. muelleri tuber infected by Fusarium. The fungi isolates were identified phylogenetically based on the similarity of Internal Transcribed Spacers (ITS) sequence. Both fungi were antagonistically assessed based on the dual culture method. The antagonistic assay showed that the two isolates of Trichoderma had the potency to inhibit the growth of the two isolates of Fusarium. Trichoderma sp. 2 has higher antagonistic potency than Trichoderma sp. 1. Based on ITS sequence similarity, Trichoderma sp. 1 and Trichoderma sp. 2 were identified as Trichoderma longipale and Trichoderma spirale respectively, while both pathogenic Fusarium were identified as Fusarium oxysporum. Trichoderma spirale therefore could be developed as a biopesticide agent in controlling Fusarium oxysporum.